School Library Resources Provision and Utilisation in Selected Secondary Schools in Sagamu Local Government Area, Ogun State, Nigeria - OYEDIPE, WURAOLA JANET; OKEWALE, OLUWATOYIN SEIDAT; ADEKUNMISI, SOWEMIMO RONKE; BURAIMO, OLAYINKA (MiddleBelt Journal of Library and Information Science, 2020)
Functional school library with resources provision and utilization remained an asset in a school setting. Despite the benefits that can accrue to students and teachers, when functional library and relevant library resources are provided, it has been observed that most secondary schools do not have functional libraries to meet their information needs. Thus, this study investigated school library resources provision, utilization and challenges in five senior secondary schools in Sagamu Local Government Area of Ogun State. The descriptive research design of ex-post-facto type was used. A sample of 340 out of 1, 698, SSS2 and SSS3 students in the five secondary schools constituted the respondents for the study. A structured questionnaire and observation method were used to collect data. Out of the 340 questionnaire administered, 303 copies were retrieved and all were found usable. The response rate was 89.12%. Many findings were discovered amongst which were; availability of obsolete and unattractive textbooks, story books and other print resources. Audiovisuals and multimedia resources were less available. The students has brought their textbooks and class notes to their school libraries to complete assignments (34.3%) and read/prepare for examinations (32.09%). A large percentage (57.8%) considered their school libraries grossly inadequate for academic use. The study however recommended adequate financial supports from government, philanthropists, parents and individuals in the society; aggressiveness on the part of principals and other senior personnel of the school as well as recruitment of qualified media specialists or school/teacher librarians amongst other recommendations.